Comparison of Tegoprazan- and Lansoprazole-Based Fourteen-Day Triple Therapies as First-Line Treatments for Eradication - Seokin Kang; Nam-Hoon Kim; Seokhyeon Jeong; Jong Wook Kim; Jung Rock Moon; Yoon Suk Lee; Jun Hyuk Son (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Objectives Tegoprazan, a novel potassium-competitive acid blocker with rapid and effective antisecretory activity, was approved for the treatment of Helicobacter pylori infections in Korea in March 2020. However, real-world data regarding tegoprazan-based therapies are scarce. We compared the efficacies of tegoprazan- and lansoprazole-based triple therapies (TTs). Methods Between March 2020 and February 2023, this study enrolled patients diagnosed with H. pylori infections who were prescribed either 14-day tegoprazan- or lansoprazole-based TTs as first-line treatments. Their medical records were retrospectively reviewed to compare H. pylori eradication rates and the rates of patient adherence to the recommended therapy. Results A total of 670 patients diagnosed with H. pylori infections were prescribed 14-day TT regimens between March 2020 and February 2023 at Ilsan Paik Hospital (Goyang, Korea). Of those enrolled in the study, 64 received tegoprazan-based TT and 295 received lansoprazole-based TT as their first-line treatment. The H. pylori eradication rates for tegoprazan- and lansoprazole-based TTs were 76.6% and 75.6%, respectively, in the intent-to-treat population; the rates were 88.9% and 88.4%, respectively, in the per-protocol population (non-inferiority test, p=0.03 and p=0.01 in the respective populations). No significant differences were observed between the two groups with regards to treatment adherence rates (84.4% vs. 85.1%, p=0.78). Conclusions As a first-line treatment for H. pylori eradication, 14-day tegoprazan-based TT demonstrated non-inferior efficacy compared with 14-day lansoprazole-based TT.